Nâng cao chất lượng công tác tổ chức sự kiện trong hoạt động thông tin - thư viện - Trần, Thị Trà Vi (Cục Thông tin khoa học và công nghệ quốc gia, 2023)
Event organization in information - library activities is a process of combining resources inside and outside the library to generate ideas, plan, implement, report and evaluate the results of event implementation with the information user as target audience. Through organizing events, the information - library agencies promote the brand as well as its products and services, stimulate information user’s demand to entice them to use and facilitate librarians to improve their professional qualifications.